Effects of Th1 and Th2 cytokines on cytokine production and ICAM-1 expression on synovial fibroblasts. - Schlaak, J F (1995)
OBJECTIVES--To investigate the influence of the Th1 and Th2 lymphokines interleukins (IL)-4 and IL-13, interferon gamma (IFN gamma), and several monokines on the adhesion of mononuclear cells to synovial fibroblasts and intercellular adhesion molecule-1 (ICAM-1) expression and cytokine production of synovial fibroblasts in patients with osteoarthritis. METHODS--Synovial fibroblasts were isolated from patients with osteoarthritis and stimulated with IL-1 beta, IL-4, IL-6, IL-10, IL-12, IL-13, tumour necrosis factor alpha (TNF alpha), and IFN gamma. Subsequently, we determined the production of IL-1 alpha, IL-1 beta, IL-6, IL-10, IL-12, IFN alpha and TNF alpha, and the expression of ICAM-1 lymphocyte function associated antigen 3 (LFA-3), BB7, and major histocompatibility complex class II molecules on these cells. Furthermore, the adhesion of freshly isolated mononuclear cells from the peripheral blood was tested using a colourimetric cell-cell adhesion assay. RESULTS--Only production of IL-6 and the expression of ICAM-1 were observed. IL-1 beta and TNF alpha were the most potent stimulatory mediators of both cytokine production and ICAM-1 expression. IL-4 and IL-13 had differential effects as they upregulated cytokine production but downregulated IFN gamma induced ICAM-1 expression. In functional adhesion assays, TNF alpha, IL-1 alpha and, to a lesser extent, IFN gamma led to increased adhesion of mononuclear cells, whereas IL-4 and IL-13 had no effect. CONCLUSIONS--Our data indicate that Th1 and Th2 lymphokines can modulate the function (cytokine production and expression of adhesion molecules) of synovial fibroblasts.